An application of a new method in permafrost environment assessment of Muli mining area in Qinghai-Tibet Plateau, China - Cao, Wei; Sheng, Yu; Qin, Yinghong; Li, Jing; Wu, Jichun (Environmental Earth Sciences, 2011)
The permafrost environment in the Muli mining area, an opencast mining site in the Qinghai-Tibet Plateau, China, is now undergoing significant degradation because of the ongoing mining activities. The permafrost environment in this mining site had already been evaluated by previous study, in which analytic hierarchy process was applied. Although this method can roughly characterize the permafrost environment of this mining site, it has limitations by being easily affected by man-made factors. In view of this limitation, this study attempts to employ a new method, the catastrophe progression method, to estimate the current stage of the permafrost environment in this mining area. The results show that, by catastrophe progression method, currently the calculated indexes of the permafrost freezing-thawing disintegration, permafrost thermal stability, permafrost ecological fragility, and the permafrost environment are 0.43 (general situation), 0.77 (general situation), 0.71 (bad situation) and 0.83 (general situation), respectively. These values imply that the permafrost environment has been damaged by anthropologic activities to a certain degree and potentially may be further degenerated. However, at this degree, a new equilibrium stage of permafrost environment could be achieved if the current state of environmental degradation is stabilized and treatments are constructed against further damages. © 2010 Springer-Verlag.